Penggunaan Capital Asset Pricing Model Dalam Menentukan Required Return Dan Systematic Risk Saham Individual - Adita Nafisa; Doni Teguh Wibowo (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2020)
In an effort to develop the capital market industry in Indonesia, the BEI continues to educate and develop the industry in a better direction, the purpose of the BEI is not merely to focus on adding new investors, but also to invest in the capital market, which will indirectly increase the amount active investor in the Indonesian capital market. Yuk Savings Stock is a form of campaign to invite all people to become prospective investors to invest by buying shares regularly and periodically. Thus, Indonesian people began to move from saving society to investing society. This research was conducted in the field of investment analysis and portfolio studies, on the capital market. This research is an explanatory study that explains investment and portfolio analysis using the capital asset pricing model as a tool for investment decision making on individual shares with a stock research population incorporated in the IDX30 BEI index. The CAPM model can determine the minimum required return on the price of an asset from investments that are at risk under equilibrium conditions. In this study the sampling was done by non-random sampling technique in the purposive random sampling method collected through secondary data with cross section data collection techniques. This study refers to two variables namely, required return which is the expected rate of return of an investment, and Systematic risk as a measure of risk that cannot be eliminated through diversification, which is a risk that is still an issue for investors. The results showed that, the greater the value of required return, the greater the value of the stock βi and vice versa the smaller the value of the required return the smaller the value of the stock βi.